Innovative technologies in educational marketing - Veres Somosi, Mariann; Kobielieva, T. O. (WSEH, 2025)
The integration of innovative technologies into educational marketing has transformed the ways institutions attract, engage, and retain students. Digital platforms, social media analytics, artificial intelligence, and personalized communication tools enable the creation of targeted campaigns that respond to diverse learner needs and global competition. These technologies support interactive promotion, enhance institutional visibility, and strengthen brand positioning in the educational sector. By applying data-driven strategies, gamification, and virtual learning environments, educational marketing becomes more adaptive, transparent, and effective, contributing to sustainable institutional development and international recognition.
Keywords: marketing; innovative technologies; educational marketing; education; globalized world; socio-economic development; digital platforms; artificial intelligence; personalization; data-driven strategies; gamification; institutional visibility